2008
DOI: 10.1099/vir.0.83053-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous persistence of multiple genome variants of human parvovirus B19

Abstract: The species human parvovirus B19 (B19V) can be divided into three genotypes. In this study, we addressed the question as to whether infection of an individual is restricted to one genotype. As viral DNA is detectable in tissue for long times after acute infection, we examined 87 liver specimens from adults for the presence of B19V DNA. Fifty-nine samples were found to be positive, 32 of them for genotype 1, 27 for genotype 2 and four for genotype 3. In four samples, DNA of two genotypes was detected; samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
3
27
0
1
Order By: Relevance
“…The large-scale surveillance of B19 virus genotypes in Europe showed that genotype 1 infections are almost invariably detected in contemporary samples, with extremely few if any genotype 2 (or 3) infections (6,7,21). This contrasts with the frequent detection of genotype 2 variants in tissue samples or persistently infected (immunosuppressed) individuals (16,24,27,30,36). The hypothesis that these variants originate from primary infections when genotype 2 was the predominant circulating virus (30) is supported by the unusual age restrictions of type 2-infected subjects (those born before 1973 and 1963 [27,30]).…”
Section: Vol 82 2008 Rapid Evolution Of Parvovirus B19mentioning
confidence: 57%
“…The large-scale surveillance of B19 virus genotypes in Europe showed that genotype 1 infections are almost invariably detected in contemporary samples, with extremely few if any genotype 2 (or 3) infections (6,7,21). This contrasts with the frequent detection of genotype 2 variants in tissue samples or persistently infected (immunosuppressed) individuals (16,24,27,30,36). The hypothesis that these variants originate from primary infections when genotype 2 was the predominant circulating virus (30) is supported by the unusual age restrictions of type 2-infected subjects (those born before 1973 and 1963 [27,30]).…”
Section: Vol 82 2008 Rapid Evolution Of Parvovirus B19mentioning
confidence: 57%
“…These analyses, performed in different population groups and tissue samples, usually led to the detection of all different genotypes confirming the property of B19V to establish a possibly lifelong persistence in tissues. Strikingly, the frequency of genotype 2 detected in tissues is normally much higher than what is normally found for circulating virus [32][33][34]. In a European setting, the frequency of genotype 2 is highest in elder people and minimal in people born after 1960-1970, when genotype 1 becomes prevalent, therefore suggesting at that date a global replacement of genotype 2 with genotype 1, in a pattern similar to what is described for other animal parvoviruses.…”
Section: Evolutionmentioning
confidence: 58%
“…Viral DNA has been reported in lymphoid tissue, including spleen, lymph nodes, and tonsils [32,158]. Liver frequently shows the presence of B19V DNA [32,33,159], and in the heart the presence of B19V DNA is also a common finding [34], that has been the focus of an ongoing debate on its potential role in the development of cardiomyopathies [160]. Viral DNA is commonly found in synovial tissues [32,157,161] and skin [32,162].…”
Section: Virus Persistence Following In Vitro Infections Carrier Cumentioning
confidence: 99%
“…Subtype 3b viruses were all collected and/or reported during the last decade. They were found in three different non-African countries in our study as well as recently in Brazil (4) and in foreigners from North Africa and Turkey living in Germany (12). This indicates either that 3b viruses are spreading outside of Africa, or they were previously missed due to the diagnostic problems mentioned before (1,5).…”
mentioning
confidence: 69%
“…The genotype 3 sequences showed by far the largest mean genetic distance (2.38%), with a maximum distance of 4.49% (DQ408305 and NC_004295). Genotype 3 has been found in France (13), Brazil (11), the United Kingdom (3), the United States (FJ265736 [unpublished data]), and foreigners in Germany (12), and it was the most prevalent genotype in Ghana (2). Interestingly, three of our five sequences from Nigeria and all five sequences from Burkina Faso also belonged to this genotype (Fig.…”
mentioning
confidence: 99%